Effect of Hot Compress for Breast Engorgement Pain Intensity on Post Partum Mother in the Working Area of Dauh Puri Health Center - Luh Ketut Hayu Hastari (Coping: Community of Publishing in Nursing, 2013)
Breast engorgement on the post partum that is often experienced by women on the third day until the fifth post partum. This engorgement is leading to pain and if it is untreated it can lead to mastitis and impact on the scope of exclusive breastfeeding. One way to reduce pain in non pharmacology is doing a hot compress. The purpose of this study is to determine the effect of hot compresses to the painful intensity of breast engorgement in mothers post partum. This study uses a quasy experimental design with pre test and post test design with control group. The sample of 30 respondents were obtained through quota sampling technique. Then the sample was divided into two groups, that is the experimental and control groups. The data was collected using a numeric rating scale (NRS). The research results obtained that in the pre test the majority of respondents experienced moderate pain is either in the control group (nine people or 60%) and the experimental group (11 people or 73,3%). Whereas in the post test control group, most respondents experienced moderate pain,that is nine people (60%) and after it has been given hot compresses on the experimental group, most respondents experienced mild pain that is as much as 11 people (73,3%). Based on statistical tests performed using the Mann Whitney test (p <0.05) obtained significance value 0.043 <0.05, then Ho is rejected, which means there is a significant effect of the provision of hot compresses to the decrease of the intensity of breast engorgement pain. Based on these results, the nurse advises to use hot compresses as an alternative therapy in non pharmacology pain management in the post partum mothers who are experiencing breast engorgement.